2006
DOI: 10.1007/s10681-006-9259-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of South and East Asian melon, Cucumis melo L., and the origin of Group Conomon var. makuwa and var. conomon revealed by RAPD analysis

Abstract: The genetic diversity and relationship among South and East Asian melon Cucumis melo L. were studied by using RAPD analysis of 69 accessions of melon from India, Myanmar, China, Korea, and Japan. The genetic diversity was large in India, and quite small in Group Conomon var. makuwa and var. conomon from East Asia, clearly indicating a decrease in genetic variation from India toward the east. Cluster analysis based on genetic distance classified 17 groups of accessions into two major clusters: cluster I compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 28 publications
(28 reference statements)
1
61
0
Order By: Relevance
“…conomon, of Asian origin (ROBINSON; DECKER-WALTERS, 1997), found in the accession BGMEL 109, has been reported to have agronomic characteristics such as low content of soluble solids, smooth, yellow skin, white pulp colour and small seeds (TANAKA et al, 2006). In contrast, Torres Filho et al (2009) identified significant characteristics for breeding programs in this botanical variety, such as high prolificacy and high firmness.…”
Section: Resultsmentioning
confidence: 99%
“…conomon, of Asian origin (ROBINSON; DECKER-WALTERS, 1997), found in the accession BGMEL 109, has been reported to have agronomic characteristics such as low content of soluble solids, smooth, yellow skin, white pulp colour and small seeds (TANAKA et al, 2006). In contrast, Torres Filho et al (2009) identified significant characteristics for breeding programs in this botanical variety, such as high prolificacy and high firmness.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen random primers (12-mer; Bex, Japan), which were selected for their ability to detect polymorphism by Tanaka et al (2007), were used in this study ( Table 2). The PCR mixture was the same as for PS-ID analysis, but the concentration of primers was 0.5 ÎŒM.…”
Section: Rapd and Ssr Analysismentioning
confidence: 99%
“…In the last decade, the genetic diversity and phylogenetic relationship between various groups of cultivated melon have been studied using analysis of molecular polymorphism, which can be easily detected using various types of DNA markers, such as random amplified polymorphic DNA (RAPD: Dhillon et al, 2007;LĂłpez-SesĂ© et al, 2003;Luan et al, 2008;Nakata et al, 2005;Soltani et al, 2010;Staub et al, 2000Staub et al, , 2004Stepansky et al, 1999;Tanaka et al, 2007;Yi et al, 2009), simple sequence repeats (SSRs: Dhillon et al, 2007;Garcia-Mas et al, 2004;LĂłpez-SesĂ© et al, 2002;Monforte et al, 2003;Nakata et al, 2005;Staub et al, 2000), and amplified fragment length polymorphism (AFLP: Garcia-Mas et al, 2000;Yashiro et al, 2005). These results showed distinct genetic differentiation between subsp.…”
Section: Introductionmentioning
confidence: 99%
“…C. melo is, therefore, considered the most diverse species in Cucumis (Stepansky et al 1999). Genetic diversity studies have used isozymes (Staub et al 1997;Akashi et al 2002), RFLPs (Zheng et al 1999), RAPDs (Garcia et al 1998;Stepansky et al 1999;Mliki et al 2001;LĂłpez-SesĂ© et al 2003;Staub et al 2004;Sensoy et al 2007;Tanaka et al 2007), AFLPs (GarciaMas et al 2000), ISSR and simple-sequence repeat (SSR) (Katzir et al 1996;Staub et al 2000;Daning-Poleg et al 2001;LĂłpez-SesĂ© et al 2002;Monforte et al 2003;Nakata et al 2005;Tzitzikas et al 2009) to analyze variability and relationships among melon groups. These studies have assisted in the elucidation of intraspecific relationships in melons from different origins.…”
Section: Introductionmentioning
confidence: 99%